Protein Targets of Acetaminophen Covalent Binding in Rat and Mouse Liver Studied by LC-MS/MS - Geib, Timon; Moghaddam, Ghazaleh; Supinski, Aimee; Golizeh, Makan; Sleno, Lekha (Frontiers in Chemistry, 2021)
Acetaminophen (N-acetyl-p-aminophenol; APAP) is a mild analgesic and antipyretic used commonly worldwide. Although APAP is considered a safe and effective over-the-counter medication, it is also the leading cause of drug-induced acute liver failure. Its hepatotoxicity has been linked to the covalent binding of its reactive metabolite, N-acetyl p-benzoquinone imine (NAPQI), to proteins. The aim of this in vivo study was to identify APAP-protein targets in both rat and mouse liver, and to compare the results from both species, using bottom-up proteomics and targeted multiple reaction monitoring (MRM) experiments. Livers from rats and mice, treated with APAP, were homogenized and digested by trypsin. Digests were then fractionated by mixed-mode solid-phase extraction prior to liquid chromatography-tandem mass spectrometry (LC-MS/MS) using scheduled multiple reaction monitoring (MRM) acquisition. The targeted assays were optimized based on high-resolution MS/MS data from information-dependent acquisition (IDA) using control liver homogenates treated with a custom alkylating reagent forming a positional isomer of the APAP modification on all cysteine residues, in order to build an in-house modified peptide database for targeted analysis. A list of putative in vivo targets of APAP were screened from previous in vitro studies, data-dependent high-resolution MS/MS analyses of liver digests, as well as selected proteins from the target protein database (TPDB), an online resource which references previous reports of proteins found to be modified by acetaminophen. Multiple protein targets of APAP in each species were found, while confirming modification sites. Several proteins were found to be modified in both species, including ATP-citrate synthase, betaine-homocysteine S-methyltransferase 1, cytochrome P450 2C6/29, mitochondrial glutamine amidotransferase-like protein/ES1 protein homolog, glutamine synthetase, microsomal glutathione S-transferase 1, mitochondrial-processing peptidase, methanethiol oxidase, protein/nucleic acid deglycase DJ-1, triosephosphate isomerase and thioredoxin. The targeted method afforded better reproducibility for analysing these low-abundant modified peptides in highly complex samples compared to traditional data-dependent experiments.